EFL Students’ Experience of Online Writing Class during Covid-19 - Suhartini Syukri; Fitryani Fitryani (IAIN KENDARI, 2021)
This qualitative descriptive research discussed students' experiences during an online writing lesson. This research focuses on the questionnaire and reflection writing experience of second-semester students of English Department during the Covid-19 pandemic. The study used two indicators namely interaction and environment during online writing learning. The researcher found the experience of students affected by their environment is the constraints of the internet network and the cost of purchasing quotas. It caused by some student residential areas are still in remote areas. Positively some students feel it is facilitated by online learning because it can be done flexibly. In the interaction indicator, some students find it difficult if they are not taught directly, while others find it easier to understand because they can access wider learning.Keyword: Covid-19; EFL Students’ Experience; Online class; Writing.